Front Cover: One‐Shot Measurement of Effectiveness Factors of Chemical Conversion in Porous Catalysts (ChemCatChem 24/2018). Issue 24 (27th December 2018) - Chmelik, Christian; Liebau, Michael; Al‐Naji, Majd; Möllmer, Jens; Enke, Dirk; Gläser, Roger; Kärger, Jörg
Abstract : The Front Cover illustrates how on‐line IR microimaging can be utilized for monitoring the mean concentration of both reactant and product molecules within an on‐going reaction by analyzing the relevant absorption bands in the IR spectrum. In their Full Paper, C. Chmelik et al. describe a procedure to determine the effectiveness factor of a chemical reaction within a porous catalyst by a single "one‐shot" measurement, exemplified by considering the hydrogenation of benzene to cyclohexane within platinum‐containing nanoporous glass beads. The front cover idea and design by Alaa Al‐Naji is greatly acknowledged. More information can be found in the Full Paper by C. Chmelik et al. onpage 5602 in Issue 24, 2018 (DOI:10.1002/cctc.201801530 ).